National Survey of Youth, 1972 - Gold, Martin ([Verlag nicht ermittelbar], 1984)
Conducted five years after NATIONAL SURVEY OF YOUTH, 1967 (ICPSR 3509), this study also was designed to measure the frequency and seriousness of delinquent activity among a representative sample of American boys and girls. Interviews were conducted in the spring of 1972 with 1,395 respondents who were 11 to 18 years old. Part 1 contains data gathered about the teenager's and his or her family's characteristics, including job history, family size, parents' education, attitudes toward school, school grades, peer group activities, dating history, self image, body image, physical health and maturation, attitudes about authority and youth culture, relationship with parents, political opinions and participation, and job aspirations. Part 2 contains each respondent's indication of which of 17 specific offenses he or she had committed in the previous three years. Information was coded on up to three incidents of each type of delinquency for each respondent. Data detailing the circumstances of each offense is also included. The 17 offenses are: (1) hitting a parent, (2) skipping school, (3) damaging property on purpose, (4) trying to get something by lying about age or identity, (5) trying to get something by lying about what you would do for a person, (6) taking something not belonging to you, even if you return it, (7) hurting or injuring someone on purpose, (8) threatening to hurt or injure someone, (9) trespassing on property, (10) trespassing in a house or building, (11) drinking beer or liquor without parental permission, (12) smoking marijuana, (13) using drugs (other than marijuana) or chemicals, (14) taking part in a fight with friends against other kids, (15) carrying a gun or knife, (16) taking a car without permission of the owner, and (17) "going all the way" with a member of the opposite sex. All but one offense match the list presented in the 1967 study. The additional offense, marijuana use, was added to reflect changes in American society since the first study was done.